Análise de um procedimento simplificado de coleta de escarro para avaliação da atividade bactericida precoce de fármacos contra o Mycobacterium tuberculosis - Nascimento, Cristina Paula do (2011)
In clinical trials studies on new drugs against tuberculosis, the main methodology used is the evaluation of the early bactericidal activity (EBA), which quantifies the decrease of CFU of Mycobacterium tuberculosis in sputum samples during the first 2 days of treatment, through 12 to 16 hours of nocturnal sputum collections. However, the sputum collection for a period of 12 to 16 hours has several shortcomings. In this context, we proposed to develop and evaluate a simple, less time-consuming procedure for sputum collection that does not require hospitalization and presents the same efficiency as a 12-hour collection procedure. We performed quantitative cultures of sputum to measure the bacterial load after three different procedures: 5-hour and 12-hour sputum collections. So this study was divided into two stages. In the first step, the bacillary loads observed in sputum were compared to those obtained after a 5-hour (6,17 log10CFU/mL) and 12 hour (6,23 log10CFU/mL) collection, and there was no statistically significant difference (p =0,27). For the second stage, the patients underwent 4 procedures for sputum collection on consecutive days - two 5-hour collections and two 12-hour collections, in order to analyze the bacterial load variation intra and inter-patients. When the intra-patient variation in the bacillary load was compared between the procedures lasting 5 hours (0,037 Log10CFU/mL) and 12 hours (- 0,022 Log10CFU/mL), no statistically significant difference was observed (p = 0,56). Moreover, the morning collection has reduced the inter-patient variation and improved the accuracy for estimation of the average change in bacterial load from a collection of one day to the other (standard error for 5-hour =0,019 and standard error for 12-hour =0,028). These results show that a 5-hour morning sputum collection is as representative as that provided by a 12-hour overnight collection. In conclusion, the simplified procedure of sputum collection for a period of 5 hours proposed by this study could be used in clinical assessment of EBA as an alternative to 12-hour collections, with no impairment to the EBA evaluation of the study drug.